Palestinian Autonomy, Self-Government & Peace - Sicherman, Harvey (Boulder Westview Press, 1993)
Many questions are examined in this book, such as what precisely does the concept of autonomy and self-government encompass?; how did the idea originate?; what kind of rights and responsibilities does it imply?; what are the chances for its success?; is it a good idea?
Includes bibliographical references. "Published in cooperation with the Washington Institute for Near East Policy." Previously published: Palestinian self-government (autonomy). Washington, D.C. : Washington Institute for Near East Policy, 1991. With new introd.
Keywords: Palestinian Arabs--Politics and government; Autonomy; Middle East; Egypt. -- Treaties, etc. -- 1978 September 17 (Framework for Peace in the Middle East)